2019
DOI: 10.1152/ajpregu.00112.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac baroreflex hysteresis is one of the determinants of the heart period variability asymmetry

Abstract: In heart period (HP) variability (HPV) recordings the percentage of negative HP variations tends to be greater than that of positive ones and this pattern is referred to as HPV asymmetry (HPVA). HPVA has been studied in several experimental conditions in healthy and pathological populations, but its origin is unclear. The baroreflex (BR) exhibits an asymmetric behavior as well given that it reacts more importantly to positive than negative arterial pressure (AP) variations. We tested the hypothesis that the BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 79 publications
2
24
1
Order By: Relevance
“…Factors beyond direct action of autonomic nervous system influence on decelerations and accelerations (Piskorski and Guzik, 2012) such as the mechanical effects of intrathoracic pressure fluctuation related to inspiration and expiration (Klintworth et al, 2012), impact of hormones, and O 2 , electrolytes, H + as well as asymmetrical characteristic of the conduction of depolarization wave between atria and ventricles (Camm et al, 1996;Berntson et al, 1997;Guzik et al, 2011). Moreover, five-irreversible dynamics (Casali et al, 2008) as well as time irreversibility of beat-to-beat HRV and BPV were changed in response to orthostatic stress (Chladekova et al, 2012). De Maria et al (2019 have suggested that HRA is determined by cardiac baroreflex hysteresis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors beyond direct action of autonomic nervous system influence on decelerations and accelerations (Piskorski and Guzik, 2012) such as the mechanical effects of intrathoracic pressure fluctuation related to inspiration and expiration (Klintworth et al, 2012), impact of hormones, and O 2 , electrolytes, H + as well as asymmetrical characteristic of the conduction of depolarization wave between atria and ventricles (Camm et al, 1996;Berntson et al, 1997;Guzik et al, 2011). Moreover, five-irreversible dynamics (Casali et al, 2008) as well as time irreversibility of beat-to-beat HRV and BPV were changed in response to orthostatic stress (Chladekova et al, 2012). De Maria et al (2019 have suggested that HRA is determined by cardiac baroreflex hysteresis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts have been made to estimate the change in HRA during orthostasis in past. De Maria et al (2019) investigated HRA at rest in supine position and during active standing. Casali et al (2008) showed that the cardiovascular response to the vertical position in the form of changes in HRA is different for tilt and standing (the asymmetry between accelerations and decelerations in heart rate appears to be more meaningful in tilt that in standing).…”
Section: Introductionmentioning
confidence: 99%
“…This observation is somehow opposite to what expected during the physiological ageing process, which is characterised by a progressive increase of the sympathetic tone and a decrease of the vagal one. [29][30][31] This apparent discrepancy could just reflect the effect of the reduced amount of physical exercise weekly in a group of athletes used to train much more and to have high cardiac sympathetic modulation at rest. If so, a regular and strenuous endurance exercise practiced at the time of the first study 11 likely elicited a transient increase of cardiac sympathetic drive, 32 that is, reversible by the modification of training intensity, that did not represent a risk factor for the development of echocardiographic abnormalities or cardiovascular disease.…”
Section: Cardiac Risk Factors and Preventionmentioning
confidence: 99%
“…The development of nonlinear dynamics appears to be favored by an enhancement of the vagal control [9][10][11][12] and by a weakened action of the cardiac baroreflex [13]. Also the different response of regulatory mechanisms to positive or negative SAP variations and circuits imposing a certain degree of cardiorespiratory phase coupling might play an important role in producing nonlinear RR variability patterns [14][15][16].…”
Section: Introductionmentioning
confidence: 99%